Guttate Psoriasis: A Case Report - Fonseca, Sara (2019)
Psoriasis is an inflammatory, immune-mediated disease with chronic and recurrent evolution. It results from the interaction between genetic predisposition and endogenous and/or exogenous triggering factors, with an imbalance in the predominantly autoimmune immune response. In guttate psoriasis, which is more prevalent in children and young adults, the association with pharyngitis and/or tonsillitis by group A β-hemolytic Streptococcus is frequent, and the antigens will trigger the immune-mediated response in a field of greater genetic susceptibility, as evidenced by the association with the HLA-cw6 allele. Classical clinical findings include the sudden onset of numerous small papules and erythematous, desquamative plaques, usually located on the trunk, tear drop-like, or often described as droplet psoriasis. In the literature, patients with guttate psoriasis have been reported to develop plaque psoriasis. We describe the case of a 17-year-old girl with a recent history of acute streptococcal tonsillitis who had recourse to the Emergency Department for erythematous, scaly and pruritic micro-papillary lesions initially located in the palms of the hands and later dispersed in the trunk, abdomen and limbs, with appearance of erythematous and scaly plaques on the elbows. No fever. No family history of psoriasis. There were no other changes in physical examination. Based on the hypothesis of guttate psoriasis, he underwent a skin biopsy that corroborated the diagnosis. He started topical treatment, with vitamin D derivative and topical corticosteroid, and phototherapy (ultraviolet B) with favorable evolution. Maintained follow-up in Consultation with evolutionary surveillance for chronicity, namely in the form of plaque psoriasis. Keywords: Guttate Psoriasis, Streptococcal Infections, Teenager